2015
DOI: 10.1111/nan.12143
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neurodegenerative disease‐related proteins and caspase‐3 in glioneuronal tumours

Abstract: Our observations in GNT provide evidence of premature activation of mechanisms of neurodegeneration which are associated with the clinical course of epilepsy in patient with GG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 88 publications
2
15
0
Order By: Relevance
“…In ganglioglioma controls, Tbr1 nuclear labelling of dysmorphic neurons was noted in one case (Supporting Information Figure 1A); a variable proportion also showed cytoplasmic OTX1 positive labelling (Supporting Information Figure 1B) but more consistent labelling was observed with SOX2 (Supporting Information Figure 1C). Little evidence of nuclear labelling of gangliogliomas for OLIG2 was seen (Supporting Information Figure 1D) but strong labelling with calbindin as previously noted (Supporting Information Figure 1E) and also with p62 as previously reported . Dysmorphic cells in ganglioglioma infrequently labelled with MCM2 in contrast to MVNT (Supporting Information Figure 1F).…”
Section: Resultssupporting
confidence: 79%
“…In ganglioglioma controls, Tbr1 nuclear labelling of dysmorphic neurons was noted in one case (Supporting Information Figure 1A); a variable proportion also showed cytoplasmic OTX1 positive labelling (Supporting Information Figure 1B) but more consistent labelling was observed with SOX2 (Supporting Information Figure 1C). Little evidence of nuclear labelling of gangliogliomas for OLIG2 was seen (Supporting Information Figure 1D) but strong labelling with calbindin as previously noted (Supporting Information Figure 1E) and also with p62 as previously reported . Dysmorphic cells in ganglioglioma infrequently labelled with MCM2 in contrast to MVNT (Supporting Information Figure 1F).…”
Section: Resultssupporting
confidence: 79%
“…We are aware that some techniques, such as western blot, are more suitable to quantify protein abundance (GFAP and CS‐56), and for this reason we named our evaluation as semiquantitative. However, if properly done, immunohistochemistry can be quantified and several studies have done so …”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed an association of dentate gyrus (DG) pathological changes with long-term seizure histories and cognitive dysfunction suggesting a compromised regenerative capacity of the DG in a subpopulation of TLE patients (Blumcke et al, 2009; Coras et al, 2010). Further evidence suggests similar mechanisms underlying cellular aging and neurodegeneration are also widespread in other forms of epilepsy such as in developmental lesions associated with chronic intractable epilepsy (Iyer et al, 2014; Prabowo et al, 2014). …”
Section: Glial Activation – a Common Histopathological Finding In mentioning
confidence: 99%